Peran Negara dalam Menciptakan Perdamaian: Kasus Pilkada Langsung di Kab. Gianyar dan Kab. Buleleng, Provinsi Bali - A.A. Gede Febri Purnama Putra (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2009)
Until recently, Direct Local Election within its implementation have been causing potential for serious conflict in regional level. Moreover, this is always leads to anarchy which triggers national disintegration. The Local Government power manages conflicts in Local Election needed for social stability. This paper will to elaborate the cases of conflicts in Local Election of Gianyar and Buleleng Regencies. However, the intensity resulted from both of regencies is different. Difference on conflict’s intensity raised is correlated to the role of government (in this case Local Government and other related institutions) in creating strategies for conflict solution in these regencies. The Government took several non-formal strategies for those parties involved. The non-formal strategies was taken for Gianyar Regency and its illustrated through several non-formal mediations to create peace and to build better communication within the resolution. I conclude that the hard situation in creating peace for conflict resolution in Buleleng was because the formal strategy taken is actually weakening communication between those involved in conflict, thus people use wrong strategies to address their message.